Comparative Study of Non-High Density Lipoproteins Cholesterol Level and Lipid Profile in Pre-Diabetic and Diabetic Patients - Banu, Shaheena; R. Jabir, Nasimudeen; C. Manjunath, Nanjappa; Firoz, C.K.; A. Kamal, Mohammad; S. Khan, Mohammad; Tabrez, Shams (CNS & Neurological Disorders - Drug Targets, 2014)
Objectives: The present study compares the role and significance of non-high density lipoproteins (non-HDL) cholesterol level in pre-diabetic and diabetic patients. This study also compares non-HDL cholesterol level between males and females and with different age groups as well. Methods: An observational study was conducted among 3830 randomly selected individuals to envisage the association of non-HDL cholesterol and other lipid parameters with age, gender, and diabetic status. On the basis of health status, the subjects were classified as diabetic, pre-diabetic and normal. Fasting blood samples were collected and analyzed on Roche p-800 modular system. Total cholesterol, high density lipoproteins (HDL), low density lipoproteins (LDL) and fasting triglycerides were also measured. From the above mentioned parameters, the level of non-HDL cholesterol level was also calculated. Results: Significant association was observed with non-HDL cholesterol level and all other studied lipid parameters (total cholesterol, HDL, LDL and triglycerides) compared with age and gender of the subjects studied. Moreover, the calculated non-HDL level, total cholesterol and triglycerides were found to be significantly co-related with diabetic status of the patients involved in the study. However, HDL and LDL values did not show any significant association with diabetic status of the patients. Conclusion: In this study, we found that age and gender of the studied subjects are associated with non-HDL cholesterol. Moreover, our data clearly indicates the positive association of non-HDL cholesterol level with pre-diabetic and diabetic status of the patients. Based on our study, we recommend estimation of non-HDL level in routine clinical practice to differentiate pre-diabetic and diabetic patients.
Keywords: non-high density lipoproteins cholesterol